Balanced Time Perspective as a Pathway to Flourishing: Examining the Role of Gratitude and Sense of Positive Agency - Peeyush Anand; Rabindra Kumar Pradhan (Changing Societies & Personalities)
Time is a human’s biggest ally. Balanced Time Perspective (BTP) is one of the crucial variables in the psychological exploration of time. BTP is characterized by a balance between past, present, and future times, essential for flourishing. Using the construal level theory, the present study investigates the influence of BTP on flourishing. The study also examines the mediating role of gratitude and a sense of positive agency in the above-mentioned relationship. Data were collected from 521 respondents (66.6% male, 33.4% female) aged 18 to 29 years across various regions as well as belonging to different residential settings, with 48.6% residing in urban areas, 25.9% in semi-urban areas, and 25.5% in rural areas of India using a purposive sampling method. The sample consisted of individuals with diverse educational qualifications, including undergraduate, postgraduate, and PhD degree holders, and represented both working and non-working individuals. Well-standardized instruments were used to measure the study variables. The data were analyzed using Jamovi software (Version 2.3.26). The results revealed that BTP significantly predicted flourishing both directly and indirectly via gratitude and a sense of positive agency. This study is among the first to explore these mediating relationships, advancing scholarly understanding of how BTP facilitates flourishing. Implications of the study are discussed in the light of study findings.